On the time-dependency of MAC curves and its implications for the EU ETS - Martin Hintermayer; Lukas Schmidt; Jonas Zinke (Institute of Energy Economics at the University of Cologne (EWI), 2020)
Recently, several articles rely on marginal abatement cost (MAC) curves to analyze the EU ETS. While the assumptions on MAC curves drive the results, the prevailing literature on the EU ETS does not take the shape of MAC curves into account. This paper discusses the implications of MAC curve properties for the EU ETS. With a partial equilibrium model of the European power sector, we derive two essential properties of MAC curves: First, the shape of MAC curves is convex and depends on economic developments, e.g., fuel prices and interest rates. Second, MAC curves flatten over time, mainly due to enlarging investment opportunities. With convex MAC curves, marginal abatement costs in the EU ETS increase over time, which triggers higher banking of firms. On the contrary, flattening MAC curves over time lead to lower incentives for banking. In particular, short-term MAC curves are steep and thus, raise the price path.
Keywords: C61; H23; Q41; Q58; 330; EU ETS; Marginal Abatement Cost Curves; Emission Abatement; Power Sector Modeling